Intravascular haemolysis with haemoglobinuria in a splenectomized patient with severe Plasmodium knowlesi malaria - Barber, Bridget E. (Malar J, 2016)
BACKGROUND: Haemoglobinuria is an uncommon complication of severe malaria, reflecting acute intravascular haemolysis and potentially leading to acute kidney injury. It can occur early in the course of infection as a consequence of a high parasite burden, or may occur following commencement of anti-malarial treatment. Treatment with quinine has been described as a risk factor; however the syndrome may also occur following treatment with intravenous artesunate. In Malaysia, Plasmodium knowlesi is the most common cause of severe malaria, often associated with high parasitaemia. Asplenic patients may be at additional increased risk of intravascular haemolysis. CASE PRESENTATION: A 61 years old asplenic man was admitted to a tertiary referral hospital in Sabah, Malaysia, with severe knowlesi malaria characterized by hyperparasitaemia (7.9 %), jaundice, respiratory distress, metabolic acidosis, and acute kidney injury. He was commenced on intravenous artesunate, but1 day later developed haemoglobinuria, associated with a 22 % reduction in admission haemoglobin. Additional investigations, including a cell-free haemoglobin of 10.2 × 10(5) ng/mL and an undetectable haptoglobin, confirmed intravascular haemolysis. The patient continued on intravenous artesunate for a total of 48 h prior to substitution with artemether–lumefantrine, and made a good recovery with resolution of his haemoglobinuria and improvement of his kidney function by day 3. CONCLUSIONS: An asplenic patient with hyperparasitaemic severe knowlesi malaria developed haemoglobinuria after treatment with intravenous artesunate. There are plausible mechanisms for increased haemolysis with hyperparasitaemia, and following both splenectomy and artesunate. Although in this case the patient made a rapid recovery, knowlesi malaria patients with this unusual complication should be closely monitored for potential deterioration.